Diagnóstico Ambiental e identificação de impactos negativos no bairro do Baralho, Bayeux - PB - Rodrigues, Adriano Pereira (2015)
The present work is a dissertation research aimed to study negative environmental impacts on Deck District in the city of Bayeux-PB. The neighborhood was the cradle of civilization bayeense, it literally settled in the mangrove ecosystem, currently with a population of about 2,300 inhabitants has gone through various environmental, economic and social problems. The research aims to identify and diagnose the processes of environmental degradation caused by social action in the community, for it was necessary to identify the environmental impacts seeking to understand the determining factors in the degradation process; Quantify and qualify the elements that are descaracterizancion the environment in question and present themselves as use conflicts, and analyze the social and environmental structure and know the relationships that people have with the mangrove ecosystem. For the implementation of the following research methodologies were adopted: the use of the checklist as a tool to identify the main negative impacts; Matrix applied to the Environmental Quality Index (AQI) which allowed quantification of those impacts and to identify the main degraded areas, as well as interviews to understand the environmental issue of population using the saturation Theoretical sampling as a technique. According to scientific research, the Deck is characterized as an average degradation of the neighborhood where the environmental impacts are identified discontinuously, such as the population is also distributed unevenly across the neighborhood area, he literally hid their elements natural and rivers: Paroeira and Sanhauá beyond the mangroves that turned just in deposits or under who were looking for a "no man's land" to settle. In practice, rivers and mangroves have no owner, or are incipient initiatives to monitor, protect and enhance these natural elements. The predatory action of human beings in the misuse of the ecosystem has left sequels in the Environment. The lack of social planning, policy and environmental, have caused considerable damage to the ecosystem.